IPF, comorbidities and management implications: Patient case 1 - Kreuter, Michael (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and follow-upThe patient was a 54-year-old man who presented with mild dyspnoea, a persistent cough and “velcro” crackles. He worked as a carpenter and smoked (10 pack–years) until 14 years ago. He had arterial hypertension and suffered a deep vein thrombosis 2 years ago. His lung function was impaired with an FVC of 70% and DLCO of 43%.[...]